The human pursuit of well-being a cultural approach - Brdar, Ingrid; SpringerLink (Online service). (New York Springer, 2011)
"This book brings together the latest research on positive psychology ... The chapters describe research and practice from diverse fields of positive psychology, covering topics such as happiness and well-being, motivation and goals, personality, academic performance and coping, measurement and interventions. The book emphasizes a cultural approach to the human pursuit of well-being. ... It presents research from a range of cultures, such as Russia, Croatia, and Egypt, in addition to ten different Western cultures. This approach helps broaden our understanding of those aspects of human experience that make life worth living in diverse cultural conditions"--From publisher's description.
Contents of pt. 1, Happiness and well-being: Can we get happier than we are? / Ruut Veenhoven -- Self-serving attributional bias and hedonic and eudaimonic aspects of well-being / Pilar Sanjuán, Alejandro Magallares, and Rodolfo Gordillo -- Affect specificity as indicators of national well-being : representative sample of Croatia / Zvjezdana Prizmić-Larsen, Ljiljana Kaliterna Lipovčan, and Tihana Brkljačić -- The effect of leisure activities on life satisfaction : the importance of holiday trips / Jeroen Nawijn and Ruut Veenhoven -- From flow to optimal experience : (re)searching the quality of subjective experience throughout daily life / Teresa Freire -- Gender differences in psychological well-being and distress during adolescence / Dalila Visani, Elisa Albiere, Emanuela Offidani, Fedra Ottolini, Elena Tomba, and Chiara Ruini -- The impact of positive affect : two weekly assessment studies on benefits of positive emotions in patients with a chronic painful disease / Elin Strand -- Studying predictors of posttraumatic growth in cancer patients / Marta Scrignaro, Sandro Barni, Maria Luisa Bonetti, and Maria Elena Magrin. Contents of pt. 2, Motivation and goals: It's all about me : maladaptive self-focused attention as a mediator of the relationship between extrinsic goals and well-being / Mami Yamaguchi and Jamin Halberstadt -- The relation of intrinsic and extrinsic aspirations to adolescent life satisfaction / Marina Merkaš, Zora Baboteg-Šarić, and Dubravka Miljković -- Where does the motivation for the antiretroviral therapy come from? : assessing existential meaning, personal growth, and motivation toward antiretroviral therapy in people affected by HIV/AIDS / Krzysztof Szadejko and Gabriele Covotta. Contents of pt. 3, Personality: The relationships between temperament, character strengths, and resilience / Ann-Marie K. Hutchinson, Anita D. Stuart, and Hester G. Pretorius -- Character strengths and well-being : are there gender differences? / Ingrid Brdar, Petra Anić, and Majda Rijavec. Contents of pt. 4, Academic performance and coping: Optimistic attributional style as a predictor of well-being and performance in different academic settings / Tamara O. Gordeeva and Evgeny N. Osin -- To flourish, arm, or face away : proactive, defensive and depressive patterns of self-regulated learning / Darko Lončarić -- Moderator effect of burnout in secondary school context / Charles Martin-Krumm, Marie Oger, Philippe Sarrazin, and Patrick Pelayo. Contents of pt. 5, Measurement: Factor structure of the French Ryff's Psychological Well-Being Scales for active older adults / Mareï Salama-Younes, Amany Ismaïl, Ali Montazeri, and Charles Roncin -- Further evaluation of the test-retest reliability of the Children Hope Scale and Students' Life Satisfaction Scale / Susana C. Marques, José Pais-Ribierto, and Shane J. Lopez -- Validation of the Mental Health Continuum Short Form and Subjective Vitality Scale with Egyptian adolescent athletes / Mareï Salama-Younes. Contents of pt. 6, Interventions: School interventions for promoting psychological well-being in adolescence / Chiara Ruini, Fedra Ottolini, Elena Tomba, Carlotta Belaise, Elisa Albiere, Dalila Visani, Ernesto Caffo, and Giovanni a. Fava -- Applying self-determination theory to help obese Portuguese individuals / Sónia Mestre and José Pais-Ribiero -- A school-based intervention involving massage and yoga for disadvantaged male adolescents : an exploratory study on a self-discovery program / Lesley Powell.
Electronic reproduction.
Keywords: Positive psychology; Well-being.; Happiness; Quality of life; Electronic books